Germany : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Germany. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2021)
Germany's economy contracted by just under 5 percent in 2020, outperforming most European peers. But renewed waves of infections and associated lockdowns caused economic activity to plunge again in the first quarter of this year. While the pace of mass vaccination has picked up and the economy has started to reopen, the recovery path is beset with risks, particularly with respect to the progress of the pandemic and supply shortages in major industries. The authorities have maintained appropriately accommodative fiscal and financial policies, and most measures supporting households and firms have been extended through 2021.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements; International Organizations; Monetary Policy; Observance; Germany